Neurodevelopmental outcome in children between one and five years after persistent pulmonary hypertension of term and near-term newborns - Atlan, Laetitia; Berthomieu, Lionel; Karsenty, Caroline; Gascoin, Géraldine; Arnaud, Catherine; Breinig, Sophie (Frontiers in Pediatrics, 2024)
Background: Persistent pulmonary hypertension of the newborn (PPHN) is a serious condition that affects 1 to 2 per 1,000 newborns. Scientific data report the existence of neurological developmental abnormalities between 10 and 30%, but the description of these disorders linked with this situation of cerebral hypoxia and haemodynamic failure remains poorly documented. Objective: The main goal of this study was to describe the prevalence of neuro-psychomotor developmental disorders in children aged between one and five years old who have been hospitalised at birth in a neonatal intensive care unit for the management of PPHN. Methods: All of the newborns ≥ 34 weeks of gestational age (WGA) with PPHN, treated with inhaled nitric oxide in our neonatal intensive care unit between January 2015 and December 2019 were retrospectively enrolled. An ASQ-3 standardised questionnaire, adapted to the appropriate age (12, 24, 36, 48 and 60 months) was performed by the parents. Results: Fifty-five children (81% of answers) with a median age of 36 months (11-68), whose real age was close to the one of the questionnaire (12, 24, 36, 48 and 60 months), have been included in this study. There was 47% of pathological score (borderline : less than 1 standard deviation (SD) or suspect: less than 2SD ) in at least one of the five studied domains, mainly in communication (25%) and individual and social skills (22%), despite a high overall score of 250 [220;285] out of 300 that improved with age. Conclusion: This study showed a significant prevalence of neuro-psychomotor developmental disorders which justifies making more accessible a prolonged and adapted follow-up for early and multidisciplinary screening and management of these children with PPHN history. Larger cohorts are needed to better explore long term outcome of these vulnerable term neonates.